Does additional spending help urban schools? An evaluation using boundary discontinuities - Steve Gibbons; Sandra McNally; Martina Viarengo (Institute for the Study of Labor (IZA), 2012)
Improving the educational attainment of disadvantaged students in urban schools is a priority for policy worldwide, but existing research is equivocal about the effectiveness of additional funding for achieving this objective. This study exploits anomalies in the spatial dimension of school funding policy in England to provide new evidence on this question. An area cost adjustment and other aspects of the formula that allocates central grants to Local Authorities (school districts) means that neighbouring schools with similar intakes, operating in the same labour market and facing the same prices for inputs can receive very different incomes. We find that these funding disparities give rise to sizeable differences in pupil attainment in national tests at the end of primary school. This shows that school resources have an important role to play in improving educational attainment. The results have direct implications for the current Pupil Premium policy in England.
urn:nbn:de:101:1-201203064110
Keywords: R0; I21; H52; 330; urban schools; education; resources; Schulfinanzierung; Wirkungsanalyse; Allgemeinbildende Schule; Bildungsniveau; Großbritannien